Cost, context, or convenience? Exploring the social acceptance of demand response in the United Kingdom. (May 2022) - Naghiyev, Eldar; Shipman, Rob; Goulden, Murray; Gillott, Mark; Spence, Alexa
Abstract: The energy sector, and buildings in particular, are one of the main contributors to climate change. Demand-Side Management (DSM) has the potential to realise energy savings on the demand as well as the supply side. However, the domestic sector still presents a major challenge due to its complex nature, one of which is the element of human interaction. A series of case studies comparing different user interface designs were undertaken to investigate domestic Demand Response (DR) in relation to automated washing appliances and their effects on occupants. Focus groups were used to inform the study design and to cross-validate case study findings. The aim was to identify factors that may influence adoption and implementation of DR, in particular incentives and feedback methods. The results highlighted the importance of the intrinsic features of the controlled appliances as well as the wider social and physical environments they were operated in. The dynamics within households with limited resources, such as time and space, meant that convenience was key regarding DR system adoption, whilst financial incentives were suitable for initial user attraction. Dynamic pricing, commonly featured in DSM systems, was also shown to stress household practices and to cause both, efficient and inefficient energy use, if coupled with automation. Furthermore, the agency, clarity and reliability of control and feedback mechanisms were found to be crucial with regards to DR acceptance. The study suggests that convenience, including ease of system operation and household practice integration, should be DR's primary guiding design principle. Highlights: Domestic demand response (DR) incentivisation should focus on convenience over money. Household practices and dynamics can determine DR's uptake and efficient use. Appliance features and external factors, e.g. weather and space, affect adoption. Agency, clarity and reliability of DR's control and feedback are crucial. Demonstrated method of generating a dynamic real-time pricing tariff.